Explaining differences in age at autism spectrum disorder diagnosis: A critical review - Daniels, Amy M; Mandell, David S (Autism : the international journal of research and practice, 2014)
The diagnosis of autism is often delayed, which translates into a missed opportunity to provide treatment during a critical developmental period. This study reviews studies that assessed factors associated with age at autism spectrum disorder diagnosis and provides recommendations on future research, programs, and policies to improve early detection. A search for all peer-reviewed articles containing the words autism, age, and diagnosis in either the title or abstract was performed. A total of 42 studies published from January 1990 through March 2012 were identified. Mean age at diagnosis for all autism spectrum disorders ranged from 38 to 120 months and has decreased over time. Factors associated with earlier diagnosis included greater symptom severity, high socioeconomic status, and greater parental concern about initial symptoms. Family interactions with the health and education systems prior to diagnosis also influenced age at diagnosis. Geographic variation in age at autism spectrum disorder diagnosis was identified in a number of studies, suggesting that community resources and state policies play a role in early identification. Early detection efforts should include enhanced parental and provider education on the early recognition of developmental problems, interventions aimed at streamlining the process from first concern to eventual diagnosis, and strategies that target underserved populations.